UNDERSTANDING DUFOURMENTEL FLAP DESIGN - CHANDRA, RAMESH; SINGH, ARUN KUMAR (Indian Journal of Plastic Surgery, 1985)
Dufourmentel flap is a local transposition flap for rhombic defects. The details of its geometrical design have been discussed. Paper models and experimental study on canine skin have also been undertaken to study the biomechanics of this flap for better understanding.